Дослідження вмісту мікроелементів у пластових водах - Mykhailovska, Olena (Збірник наукових праць Галузеве машинобудування будівництво, 2018)
The content of trace elements of iodine, bromine in the stratal waters of Chyzhivsk and Bilsk field has been analyzed. Deposits with high content of iodine and bromine ions are studied. The connection has been detected between the high content of iodine in underground water and their mineralization depending on the respected thermobaric conditions. It has been established that stratal waters of Chyzhivsk and Bilsk fields can be attributed to iodine-bromine. The analyzes has revealed that waters of the Chyzhivsk and Bilsk fields can be used for industrial removal of iodine and bromine. Having analyzed the data on the field, it has been determined that ground waters of the disclosed Chyzhivsk and Bilsk field complex cannot be used for amelioration purposes because of their high mineral content.